THE RAILWAY TRANSPORT SYSTEM OF REFORMED RUSSIA: FEATURES OF DEVELOPMENT IN THE CONTEXT OF THE INDUSTRIAL REVOLUTION (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article explores the development of the railway transport system in post-reform Russia during the industrial revolution in the second half of the 19th century. Drawing on a wide range of historical and economic sources, the study analyzes the structural, economic, and institutional factors that shaped railway expansion. Particular attention is paid to the role of the state, military, and private capital in financing and operating the railway network. The article argues that the railways acted as a key catalyst for industrial growth, internal market integration, and regional transformation. Through a comparative approach, the Russian experience is contextualized within broader European modernization trends. The study contributes to understanding how transport infrastructure influenced economic and social modernization in the Russian Empire.